(untitled) (Journal for Studies in Humanities and Social Sciences, 2017)
High levels of unemployment in Namibia, skills shortages and the pressure to compete both locally and internationally, require organisations to satisfy basic psychological needs of employees. Basic psychological needs have been identified as critical ingredients for employees to grow, develop integrity and remain healthy (autonomy, relatedness, competence). Turnover intention is a damaging attitude towards the organisation that lasts long after the employee has left. The aim of this study was to assess the relation between basic psychological need satisfaction and turnover intention within the insurance, telecommunication and teaching industries in Windhoek. Employees are less likely to leave an organisation if they experience satisfaction in terms of autonomy, competence and relatedness. A cross-sectional survey design was used, employing questionnaires to collect data on the biographical details, basic psychological need satisfaction and turnover intention of employees in the Khomas region. The sample consisted of an insurance firm (n=85), a telecommunication provider (n=37) and different Governmental Secondary Schools (n=104) in Windhoek. The relationship between basic psychological need satisfaction (as measured by the Work-Related Basic Psychological Need Satisfaction Scale) and turnover intention (as measured by the Turnover Intention Scale) was investigated making use of Spearman’s rank order correlation. A negative correlation was found between competence and relatedness [r = -.15, n=226, p < .05]; an insignificant relation between competence [r = -.01, n=226, p < .05] and turnover intention; and between relatedness and turnover intention [r = .10, n=226, p < .05]. When employers and managers know how to ensure satisfying interactions and how they manage employees, provide employees with the necessary autonomy; and improve their perceived levels of competence, a reduction of turnover intention, coupled with other positive work related attitudes, becomes likely.